Application of backward design in designing learning with the observation-based learning method - Yusuf Nugraha Dano Ali; Laksmi Dewi (Curricula: Journal of Curriculum Development, 2023)
Nowadays, teachers must be more creative and professional in developing learning activities, and teachers have to follow the proper procedure to meet the needs and challenges in the future. For that reason, teachers need to change how they design learning activities. Making the right learning design is the first step for teachers and students to have a meaningful learning process. A good learning design is planned by professional teachers who understand their teaching duties and how the design can make a good learning system. This article offers solutions for teachers to make a good learning design that fits the demands of a modern curriculum called Backward Design. Using Backward Design can help teachers focus on learning to fulfill the goals made and structured in their plan. Backward Design is also easy to develop for students to understand and helps evaluate the learning process easily. Learning design with observation-based learning can increase the students ‘ creativity, productivity, creativity, innovation, and practical students by strengthening their attitudes, skills, and knowledge. Observation-based learning also requires teachers to change their mindset in education, where they will become facilitators.   Abstrak Dimasa seperti ini seorang guru dituntut lebih kreatif dan profesional untuk mengembangkan pembelajaran, selain itu para pelaku pendidikan juga diharapkan menjalankan prosedur yang telah ditetapkan bersama sesuai dengan kebutuhan dan tantangan pendidikan dimasa yang akan datang. Untuk itu, guru perlu berubah dimulai dari bagaimana mereka merancang pembelajarannya. Perencanaan pembelajaran merupakan langkah awal dari proses pembelajaran yang bermakna. Perencanaan pembelajaran yang baik tentu direncanakan oleh guru yang paham akan tugas profesinya dalam menguasai dan memahami serta dapat merancang pembelajaran dengan baik. Artikel ini bertujuan untuk menawarkan solusi model perancangan pembelajaran yang sesuai tuntutan kurikulum modern yang disebut dengan Backward Design. Karena dengan perencanaan yang menggunakan Backward Design dapat membantu guru untuk memfokuskan pembelajaran terhadap tujuan kurikulum yang disusun dan sangat mudah untuk dikembangkan serta pendalaman pemahaman siswa dan transfer pembelajaran pun dapat dievaluasi dengan mudah. Pembelajaran yang disusun mengedepankan pengalaman personal melalui proses observation based learning ini, dapat meningkatkan kreativitas siswa, menghasilkan siswa yang produktif, kritis,  kreatif, inovatif, dan afektif melalui penguatan sikap, keterampilan, dan pengetahuan yang terintegrasi. Observation-based learning juga menuntut para guru untuk mengubah mindset dalam proses pembelajaran dimana mereka akan lebih banyak menjadi fasilitator. Kata Kunci: Backward Design; observation-based learning; perencanaan pembelajaran